The yeast homolog of the U1 snRNP protein 70K is encoded by the SNP1 gene. - Kao, H Y (1992)
The product of the yeast SNP1 gene has high homology to two domains of the metazoan U1 snRNP protein 70K, which binds to stem/loop I of the U1 RNA. However, the absence of other domains conserved in metazoan 70K and the minimal effect of yeast U1 RNA stem/loop I deletion make the assignment of SNP1 as yeast 70K less clear. To address this question, we have expressed the SNP1 gene as a fusion protein in E. coli and developed a gel shift assay for U1 RNA binding. We show here that the product of the yeast SNP1 gene binds directly and specifically to the first 47 nucleotides of yeast U1 RNA, which include the stem/loop 1 structure. We therefore conclude that the SNP1 gene product is the yeast 70K homolog. This is the first yeast protein to be identified as a homolog of a metazoan snRNP protein.